Sustainable consumption in the clothing segment: a comparative study between Brazilians and Germans - Chaves, Letícia Benevides; Carneiro, Juliana Vieira Corrêa; Silva, Laíse do Nascimento; Murakami, Luiz Carlos; Teixeira, Linnik Israel Lima (Revista de Administração da UFSM, 2022)
Objective – To Analyze and compare sustainable consumption habits in the clothing segment between Brazilians and Germans. Design/methodology/approach– Descriptive, exploratory, and qualitative research. Interviews were conducted with 15 Germans and 15 Brazilians, aged between 20 and 32 years old, in order to identify consumption habits in the clothing segment, familiarity with the theme: sustainable consumption , and levels of personal awareness regarding their consumption behavior, applying the content analysis based on Bardin (2011) as a technique. Findings – A significant difference between the two groups was found. While Germans presented greater knowledge on the subject, which was converted into embracing sustainable conduct in the clothing segment, Brazilians demonstrated to have a more superficial knowledge, besides presenting lower levels of awareness in their consumption and sustainable practices in the analyzed segment. Therefore, it concludes that Germans have greater access to information on the theme and more interest and familiarity with the subject. Consequently, it showed that it influences their consumption behavior, presenting habits towards environmental, social, and economic concerns in the clothing segment, habits that were not identified in the Brazilian sample group. Originality/value (mandatory) – It contributes by providing an opportunity to comparatively analyze the habits and consumption of two distinct countries, helping entrepreneurs and managers to understand the market segments better and create more powerful strategies, focusing on the value perceived by the customer in the acts of consumption.